Exploration of the blocking effect of Fab fragment of IgG autoantibody on erythrocyte autoantigens - Haitao HUANG; Xuehong WEN (Zhongguo shuxue zazhi, 2024)
Objective To use Fab segments of autoantibodies to bind to autoantigens on red blood cells in order to block the binding of intact autoantibodies to the autoantigens. Methods The pure autoantibodies were obtained from the serum of patients by absorption and elution test, then Fab segments were obtained by hydrolyzing IgG autoantibodies at 37℃ overnight with papain enzyme. The Fab segments were used to bind the corresponding autoantigens specifically, thus blocking the binding of intact autoantibodies to autoantigens. Results The pure autoantibodies obtained through absorption and elution test were all hydrolyzed by papain to generate Fab fragments. When mixed with intact autoantibodies in their respective elution solutions, these Fab fragments were able to block the binding of intact autoantibodies to red blood cell autoantigens. Among the three samples, there was a mutual blocking effect between sample 1 and sample 2, while no mutual blocking effect was observed between sample 2 and sample 3. Conclusion Fab segment of autoantibody can eliminate the agglutination of intact autoantibodies and erythrocyte autoantigens, and can be applied to clinical practice to solve clinical problems.